Depression and Anxiety as Key Factors Associated With Quality of Life Among Lung Cancer Patients in Hai Phong, Vietnam - Khue, Pham Minh; Thom, Vu Thi; Minh, Dao Quang; Quang, Le Minh; Hoa, Nguyen Lam (Frontiers in Psychiatry, 2019)
Background: Cancer is a leading cause of death. People living with cancer experience a variety of symptoms that might profoundly affect their quality of life (QoL). Objective: The study aims to identify factors associated with the quality of life of patients with lung cancer at the oncology department of Viet Tiep hospital, Hai Phong city, Viet Nam in 2018. Methods: A cross-sectional study was conducted to collect the data from lung cancer inpatients in Hai Phong city, Vietnam. The EQ-5D-5L and the EQ-visual analogue scale (EQ-VAS) were used to assess health-related quality of life (QoL). A multivariable regression analysis was performed on the EQ-5D utility score and the EQ-VAS score as dependent variables, and socioeconomic, social support, and psychological factors as potential predictors. Results: A total of 125 lung cancer patients were invited to participate in this study. The highest proportion of respondents reporting any problems was in anxiety/depression (92.8%), pain/discomfort (81.2%), usual activities (75.2%), and mobility (60%) dimensions, while the lowest percentage was in self-care dimension (40.8%). The multivariate analyses showed that a low QoL score was significantly associated with depression, incapacity to pay, low response to treatment, presence of side effects. Conclusion: QoL of lung cancer patients is associated with anxiety/depression and other factors that can be modified by specific interventions. It is therefore possible to take care of psychological aspects to improve the QoL of Vietnamese people suffering from this condition.